Rapid diagnosis of gram negative pneumonia by assay of endotoxin in bronchoalveolar lavage fluid. Issue 7 (July 1992) - Pugin, J; Auckenthaler, R; Delaspre, O; van Gessel, E; Suter, P M
Abstract : BACKGROUND: Diagnosis of ventilator associated pneumonia can be made by quantitative cultures of bronchoalveolar lavage fluid or of protected specimen brushings, though cultures require 24-48 hours to provide results. In 80% of cases aerobic Gram negative bacteria are the cause. METHODS: A rapid diagnostic method of assessing the endotoxin content of lavage fluid by Limulus assay is described. Forty samples of lavage fluid were obtained from patients with multiple trauma requiring mechanical ventilation for a prolonged period. Pneumonia was diagnosed on the basis of clinical, radiological, and bacteriological findings, including quantitative cultures of lavage fluid. RESULTS: A relation was observed between the concentration of endotoxin in lavage fluid and the quantity of Gram negative bacteria. The median endotoxin content of lavage fluid in Gram negative bacterial pneumonia was 15 endotoxin units (EU)/ml; the range observed in individual patients was 6 to > 150 EU/ml. In patients with pneumonia due to Gram positive cocci and in non-infected patients the median endotoxin level was 0.17 (range < or = 0.06 to 2) EU/ml. An endotoxin level greater than or equal to 6 EU/ml distinguished patients with Gram negative bacterial pneumonia from colonised patients and from those with pneumonia due to Gram positive cocci. CONCLUSION: The measurement of endotoxin in lavage fluid is a rapid (less than two hours) and accurate diagnostic method. It should allow specific and early treatment of Gram negative bacterial pneumonia.